USE OF INFORMATION AND COMMUNICATION TECHNOLOGY BY TEACHERS IN LEARNING HISTORY SENIOR HIGH SCHOOL PEKANBARU - Oemar, Kamaruddin (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
What we see when studying the subject that is being done by the subject teachers ofhistory in the classroom. Classroom atmosphere during history lessons are generally less encouraging,students look sultry and restless (Haikal, 1989). This situation shows that the less favored historicalsubjects and boring students (Isjoni, 2006). Learning the history of which only emphasizes the pastwith lead students bored and lack of interest in history lessons (Gunning, 1978). Conditions ofsubject teachers of history which mostly still not optimal, even still many who have not been ableto take advantage of advances in technology or in other words still stutter technology (Gatek).Problem formulation is: How where the availability of facilities and prarana, the principal policyto support, education and training has gained teacher and factors that constrain teachers in theuse of information and communication technology in teaching high school history Pekanbaru. Thepurpose of this study is: To determine the extent of availability of facilities and prarana, the principalpolicy to support, education and training of teachers who have acquired the necessary skills andconstraints of teachers in the use of information and communication technology in teaching highschool history Pekanbaru. The purpose of this study is: To determine the extent of availability offacilities and prarana, the principal policy to support, education and training of teachers who haveacquired the necessary skills and constraints of teachers in the use of information and communicationtechnology in teaching high school history Pekanbaru.The location and time of study. The locationwas chosen in this study is the city of Pekanbaru. When the study was conducted for 4 (four)months. The population of this study are all high school teachers who care for high school historycourses at public and private city of Pekanbaru. Samples taken as many as three SMA and threeprivate high school. Pekanbaru City some 14 teachers as respondents, with details: SMAN 5 totaling3 teachers, totaling 3 SMAN 9 teachers, SMAN 11 numbered 2 teachers, high school teachersHandayani numbered 2, SMA PGRI numbered 2 teachers, high school Tri Bakti numbered 2 teachers.Data collection techniques used in this study, such as: (1) observation, (2). Interview, (3)library;(4) Questionnaire. Data analysis techniques in this study using qualitative analysis. From the dataanalysis it can be concluded as follows: (1) Not all teachers use of ICT in teaching History (2) aproportion of the principal has been supporting the use of ICT by teachers in teaching high schoolhistory City Pekanbaru, (3) a proportion of the teachers have received training on ICT. Teachersfelt that ICT can improve the ability of teachers both in PBM and student learning outcomes, (4)Availability of hard ware and sof ware is still limited, the age factor, not confident, doubt and fearKeywords: information and communication technology, the teacher and the teaching of history